Enhancing the thermal stability of natural rubber/recycled ethylene propylene diene rubber blends through the use of bio‐compatibilizers. (17th October 2018) - Hayeemasae, Nabil; Ismail, Hanafi
Abstract : Recycling of rubber waste and searching for alternative routes to prolong the service life of rubber products are of significant concern. One of the ideas to reduce the rubber waste is to blend it with the virgin rubber to gain synergistic properties from its own advantages. In this study, natural rubber (NR) and recycled ethylene propylene diene rubber (R‐EPDM) were blended as a way to combine the mechanical properties and oxidative resistance given by NR and R‐EPDM, respectively. New approaches in enhancing the thermal stability were observed through the use of bio‐compatibilizers that is, alkanolamide (AKA)‐based refined, bleached, and deodorized palm stearin (RBDPS) and NR latex (NRL). The thermal stability of the blends was monitored through two techniques: thermo‐oxidative aging and thermogravimetric Analysis. Results indicated that the aging resistance of the blends was improved by addition of AKA and NRL as bio‐compatibilizers. This is confirmed by the enhancement of thermal decomposition temperature and the activation energies of the blends. The obtained TG profiles and the calculated kinetic parameters indicated that introducing AKA and NRL enhanced their thermal stability, especially at higher contents of AKA and NRL. J. VINYL ADDIT. TECHNOL., 25:E155–E165, 2019. © 2018 Society of Plastics Engineers